Black Beauty - Sewell, Anna; Alan Marks (London Usborne Publishing, 2005)
A poignant and moving retelling of Anna Sewell's classic novel, which follows the story of Black Beauty - the brave and noble horse that overcomes danger and cruelty to eventually find a loving home.
Includes Color Illustrations
Keywords: Adventure Story -- A terrible time -- An unexpected ending